2022
DOI: 10.1016/j.jbc.2021.101546
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective TRPC channel inhibition and suppression of aminoglycoside-induced premature termination codon readthrough by the small molecule AC1903

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Studies have shown that alterations in calcium metabolism, such as changes in the expression or activity of calcium channels, pumps, and exchangers, can lead to the development of PTC ( 12 , 37 , 38 ). For example, mutations in genes encoding calcium channels and pumps, such as TRPC3, TRPM7, and SERCA2, have been identified in PTC patients ( 39 , 40 ). These mutations have been associated with an increased risk of tumor recurrence and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that alterations in calcium metabolism, such as changes in the expression or activity of calcium channels, pumps, and exchangers, can lead to the development of PTC ( 12 , 37 , 38 ). For example, mutations in genes encoding calcium channels and pumps, such as TRPC3, TRPM7, and SERCA2, have been identified in PTC patients ( 39 , 40 ). These mutations have been associated with an increased risk of tumor recurrence and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also investigated the role of nonselective and selective transient receptor potential channel (TRPC) calcium channels in controlling SCR via cellular uptake. AC1903, a TRPC5 inhibitor, successfully suppressed G418 uptake and, hence, SCR in junctional EB patient‐derived keratinocytes with a nonsense mutation in the COL17A1 gene 56 …”
Section: Aminoglycoside Antibioticsmentioning
confidence: 99%
“…Very recently, Baradaran-Heravi et al demonstrated that TRPC cation channels influence readthrough efficiencies by controlling the cellular uptake of aminoglycosides. The inhibition of the TRPC5 channel with a small molecule (AC1903) reduced intracellular concentrations of G418 and consequently reduced the induction of PTC-readthrough in a cancer cell line (harboring a homozygous p53 nonsense mutation) and in junctional epidermolysis bullosa (JEB) patient-derived keratinocytes (harboring a homozygous mutation in COL17A1 ) [ 119 ].…”
Section: Induction Of Nonsense Suppressionmentioning
confidence: 99%